Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2014
DOI: 10.1145/2556288.2557246
|View full text |Cite
|
Sign up to set email alerts
|

"healthifying" exergames

Abstract: Exergames, video game systems that require exertion and interaction, have been rising in popularity in the past years. However, research on popular exergames shows mixed health benefits, potentially due to minimal energy expenditure and decreasing use over time. This paper presents a 2x2 experimental study (N = 44), using a popular exergame, where we vary the framing of intention (i.e., "Gameplay" or "Exercise") and feedback (i.e., "Health" or "No health") to explore their single and interactive impacts on per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 38 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Moreover, playing against a real player results in greater energy exertion than playing against a computer (Max et al, 2018; Peng & Hsieh, 2012). Additionally, for a comparable exertion (PE class for example), players during this gaming mode perceived lower effort exertion (Fogel et al, 2010) and they reported greater motivation (Chen et al, 2014). Finally, evidence is conflicting as to which multiplayer mode (cooperative vs competitive) leads to greater energy expenditure (Chen et al, 2014; Lyons et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, playing against a real player results in greater energy exertion than playing against a computer (Max et al, 2018; Peng & Hsieh, 2012). Additionally, for a comparable exertion (PE class for example), players during this gaming mode perceived lower effort exertion (Fogel et al, 2010) and they reported greater motivation (Chen et al, 2014). Finally, evidence is conflicting as to which multiplayer mode (cooperative vs competitive) leads to greater energy expenditure (Chen et al, 2014; Lyons et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Looking at current HCI work on exertion gaming, much of it focuses on in some way on energy expenditure. How much energy expenditure exertion games promote in their players has been studied in many ways, such as by augmenting existing game mechanics with exertion based bonuses or penalties (Berkovsky et al, 2012;Chatta et al, 2015;Hassan et al, 2012), creating games for school physical education classes (Keskinen et al, 2014;Macvean and Robertson, 2013), replacing conventional input devices with exertion based gestural control (Guo and Quarles, 2012), studying how much energy existing exertion games require to play (Chen et al, 2014;O'Donovan et al, 2012;Whitehead et al, 2010), and how one might motivate people to play exertion games more often (Macvean and Robertson, 2013;Nunes et al, 2014;Yim and Graham, 2007).…”
Section: Incorporating Sports and Play Into Exertion Gamesmentioning
confidence: 99%
“…We could also include in this list full body rhythm games such as Dance Dance Revolution (Konami, 1998) and Dance Central (Harmonix, 2010), which present the vigorous physical movement of dancing as enjoyable in itself, rather than primarily focusing on fitness or health goals. Even if we do wish to explicitly focus on health improvement, a recent academic study of Dance Central (Chen et al, 2014) suggests that if we do wish to explicitly focus on health outcomes, rather than building games that attempt to hide the existence of exertion and using gamification to encourage people to exert themselves, it may actually be more effective to "healthify" fun games, by framing the game as a form of exertion, something that in their study encouraged players to do exercise for longer.…”
Section: Critique 4: Fighting the Obesity Epidemicmentioning
confidence: 99%